1997
DOI: 10.1046/j.1365-2281.1997.05353.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response to CO2 in patients with snoring, obstructivehypopnoea and obstructive apnoea

Abstract: Obstructive sleep apnoea (OSA) is caused by an obstruction of the upper airway. Sufficient sensitivity to CO2 in the respiratory centre is known to be a critical factor for adequate tone in the upper airway muscles. The hypothesis of this study is, therefore, that the ventilatory response to CO2 is reduced in patients with OSA. Twenty-six patients who suffered from snoring, 19 snoring patients with obstructive hypopnoea (OH) and 33 snoring patients with obstructive apnoea (OA), were studied. The control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…However, the severity of sleep disorder in that study was measured by in-home respiratory monitoring only [34]. In addition, the HCVR value was calculated as the slope of V E /FetCO 2 , which is different from established methods of HCVR measurement [21,34]. Another study has found both increased HCVR in 14 non-hypercapnic OSAHS and decreased HCVR in 11 chronic hypercapnic OSAHS patients compared with control subjects [32].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the severity of sleep disorder in that study was measured by in-home respiratory monitoring only [34]. In addition, the HCVR value was calculated as the slope of V E /FetCO 2 , which is different from established methods of HCVR measurement [21,34]. Another study has found both increased HCVR in 14 non-hypercapnic OSAHS and decreased HCVR in 11 chronic hypercapnic OSAHS patients compared with control subjects [32].…”
Section: Discussionmentioning
confidence: 87%
“…However, the severity of sleep disorder in that study was measured by in-home respiratory monitoring only [34]. In addition, the HCVR value was calculated as the slope of V E /FetCO 2 , which is different from established methods of HCVR measurement [21,34].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A response that is either too weak or too strong could contribute to respiratory control instability resulting, for example, in upper airway obstruction. [4][5][6] A response that is too fast or too slow could also destabilise respiration. An inability to promptly correct blood gas-that is, a delay in response time in certain infants, could contribute to the onset of bouts of periodic breathing.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Very preterm infants with apnoea and periodic breathing exhibit diminished chemoreceptor responsiveness, [7][8][9] while full term infants with OSA can exhibit either subtle changes, 10 11 or normal responses to hypercapnia. 12 It can be difficult to make a clear and unequivocal distinction between different types of apnoeas.…”
mentioning
confidence: 99%